Scaling Analysis of Samara-Type Autorotating Seeds - Aerodynamic Performance and Geometric Constraints Across Varying Atmospheric and Gravitational Conditions - He, Lei (Cranfield University, 2025)
This article introduces a numerical blade element model (BEM) to capture the descent behaviour of rotating samara wings. Polhamus’s method was employed to capture the leading-edge vortices (LEVs) on the wing blade. The autorotation effects in descending maple seeds offer inspiration for passive payload delivery and planetary exploration. However, little research has analysed the feasibility domain of this effect across diverse planetary environments. Therefore, there is a need to examine this domain by studying the coupling effects of changing gravity, scale and air density. This project aims to develop a bio-inspired flying seed model with optimised scale setting for slow descent in extraterrestrial environments. Results show that gravity amplifies scaling effects, and air density sets thresholds for sustained autorotation. Descent velocity follows an √(g/ρ) trend in moderate densities of 1–4 kg/m³, but this breaks down beyond this region. The feasible region on Earth has air densities of 1.0–1.22 kg/m³, gravity range between 9.796 and 9.834 m/s², and scales of 10–40, maintaining descent around 1.5 m/s.
Keywords: Samara seeds; Autorotation; Blade Element Momentum; Leading-edge vortex; Scaling laws; Extraterrestrial environments